Islamic resurgence in contemporary Cameroon: the impact of the Tablighi Jama'at - Ayong, Ahmed Khalid (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2011)
This dissertation examines the factors behind the phenomenon of Islamic resurgence in contemporary Cameroon and focuses on the role, contribution and impact of the Tablighi Jama'at. It adopts an analytical, a critical and a historical approach in examining the reasons for the ongoing rise of Islamic awareness in contemporary Cameroon. This work argues that the methodology and strategy used by the Tablighi Jama'at - as one of the most widely followed and successful Islamic organizations in the country based on reviving and promoting Islamic consciousness within the Muslim community- has immensely contributed to Islamic religious fervor witnessed in the country during the past three decades. It highlights the reason why many Cameroonian Muslims, who are followers of the movement, believe that the Tablighi Jama'at's emphasis on self-reformation provides a better solution to the moral decadence, crisis of identity and backwardness of the Muslim community in the country. The Tablighi Jama'at is still, however, underestimated as a revivalist movement in contemporary Cameroon because it operates only within the Muslim community and does not have any political agenda. The study investigates the methodology of the Tablighi Jama'at considered controversial and questionable by its detractors. The critics claim that the Tablighi Jama'at methodology of da'wah is an unlawful innovation, arguing that it is not supported by the Qur'anic and Prophetic tradition. Furthermore, they blame the Tablighi Jama'at for putting the responsibility of da'wah in the hands of the masses instead of the ulama. Other opponents consider the movement's abandonment and aloofness from socio-political issues, sufficient reasons in preventing Cameroonian Muslims from joining the Tablighi Jama'at.